1997
DOI: 10.1037/0893-3200.11.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child interaction among depressed fathers and mothers: Impact on child functioning.

Abstract: This issue completes Volume 11 and contains the author index for the volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
4
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 57 publications
7
111
4
2
Order By: Relevance
“…In general, research has shown that the youth from depressed parents are at a greatly increased risk for a variety of psychiatric diagnoses (Hammen, 1991). Other studies have also discovered significantly higher prevalence rates of anxiety disorders, externalizing disorders, depression, and behavior problems in youth with a depressed parent (Fendrich, et al1990;Jacob & Johnson, 1997).…”
Section: Child Outcomes Associated With Parent Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, research has shown that the youth from depressed parents are at a greatly increased risk for a variety of psychiatric diagnoses (Hammen, 1991). Other studies have also discovered significantly higher prevalence rates of anxiety disorders, externalizing disorders, depression, and behavior problems in youth with a depressed parent (Fendrich, et al1990;Jacob & Johnson, 1997).…”
Section: Child Outcomes Associated With Parent Depressionmentioning
confidence: 99%
“…For example, some researchers have reported evidence that children's behaviors contribute to dysfunctional family communication patterns as well as the parent's depression (Panaccione & Wahler, 1986;Jacob & Johnson, 1997). In a study by Hops, et al (1987), researchers used home observations to assess the interactional effects between the depressed parents and their children and spouses on each other.…”
Section: The Interactional Effects Of Family Support and Parent Deprementioning
confidence: 99%
“…For example, studies show that children of illicit drug users are more likely to develop antisocial behaviors, especially drug use behavior (Fawzy, Coombs, & Gerger, 1983;Gfroerer, 1987;Jacob & Johnson, 1997). According to Wills, Sandy, Yaeger, and Shinar (2001), parental substance use is associated with lower levels of parental support and with higher levels of parent-child conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Whether it is biological or environmental depressed parents are less likely to respond positively to their children. Parents who experience depression are more likely to have negative interactions with their children from infancy through adolescence (Field 1984;Jacob & Johnson, 1997). Children of parents who are depressed can cause deleterious effects on parenting behaviors (Lovejoy et al, 2000) resulting in increased risk for externalizing behaviors (Ge et al, 1996;Heller & Baker, 2000;Kim-Cohen et al, 2005) and internalizing behaviors (Wickramarante & Weissman, 1998).…”
Section: Parental Depressionmentioning
confidence: 99%